The Influence of Tourism Products, Electronic Word of Mouth, and Physical Evidence on Visiting Decisions (Study on Blitar Park Tourism Visitors) - ruwina, khilma; Suprajang, Sandi Eka (Ekonika : Jurnal Ekonomi Universitas Kadiri, 2025)
This study aims to examine the influence of tourism products, electronic word of mouth (eWOM), and physical evidence on the decision to visit Blitar Park Tourism. This study uses a quantitative approach with a survey method, where data is obtained through a questionnaire distributed to 100 respondents who visit Blitar Park Tourism. The sampling technique used is accidental sampling. The collected data was analyzed using SPSS version 26 software to test the relationship between variables. The results of data analysis show that tourism products, electronic word of mouth, and physical evidence have a partial or simultaneous effect on the decision to visit Blitar Park tourism.